Me and My Indonesianess: How Kaskusers Express Their In-group Feelings - Pujarama, Widya (FISIP Universitas Atma Jaya Yogyakarta, 2016)
Abstract: It is asserted that new cultural hub provided by communication technology in the 21st century has driven both collectivist and individualist societies to reshape their identities. This research examines how Kaskusers, who visited Kaskus Regional Melbourne Lounge Thread, construct their collective identity by composing their profi le page. Applying Van Leeuwenâ€™s social semiotic theory, the study revealed Kaskusers were conducting self-disclosure by revealing their primary and situational identity, which mainly refl ects their cultural connection to Indonesia. To conclude, Kaskus was perceived as a utopian community where the culture-bounded â€œidealised version [of self]â€ interacted in the egalitarian environment on online site.Abstrak: Teknologi komunikasi di abad ke-21 mendorong masyarakat, baik kolektivis maupun individualis, untuk membentuk kembali identitas mereka. Penelitian ini membahas bagaimana Kaskuser yang mengunjungi thread Kaskus Regional Melbourne Lounge menuliskan profi l mereka. Berlandaskan semiotika sosial van Leeuwen, penelitian ini menemukan bahwa Kaskuser melakukan pengungkapan diri dengan menunjukkan identitas primer dan identitas situasional mereka yang mayoritas mencerminkan hubungan budaya mereka dengan Indonesia. Sebagai kesimpulan, Kaskus dianggap sebagai sebuah utopian community di mana â€œidealised version [of self]â€ berinteraksi di dunia maya yang egaliter.